A Survey of the Latest IT Trends of Cloud Software-As-A-Service - Sandy Kosasi; Alexander Harsono; I Dewa Ayu Eka Yuliani (IAES Indonesia Section, 2014)
Software-as-a-service (SaaS) is an increasingly popular IT model and has become an IT trends. Yet, research on this topic is still rare in Indonesia. The purpose of this paper is to examine the latest IT trends of Cloud SaaS system using surveys and interviews as a research method to obtain data from 130 companies. Data was analyzed using descriptive statistics approach to measure the IT trends. Findings showed the willingness to consider traditional on-premise systems steadily decreased, whereas over the same time frame, the willingness to consider Cloud SaaS systems steadily increased. This study provides managers and academia with a critical insight into the latest IT trends Cloud computing and SaaS and contributes toward IT solutions.